PENGENALAN PELUANG DAN PENGEMBANGAN KARIR DI JURUSAN PERBANKAN SYARIAH - Ridwan, Muhammad; Budimansyah, Muhammad (LPPM Universitas Potensi Utama, 2023)
This community service aims to socialize the introduction of opportunities and career development in the sharia banking department to students in class XI and XI of State Preparatory Madrasah Aliyah 4 Medan. As the financial industry develops, more and more students are interested in pursuing sharia banking education. Islamic banking is a banking system that operates based on Islamic economic principles. These principles include financial aspects that are in accordance with Islamic sharia law, known as